Effectiveness and safety of non-fixation method in cochlear implantation - Alsalami, Azzam M.A.; Rasheed, Ahmed M,; Miteab, Ragheed T, (AL-Kindy College Medical Journal, 2014)
ABSTRACTBackground: cochlear implants are electronic devices that convert sound energy into electrical signals to stimulate ganglion cells and cochlear nerve fibers. These devices are indicated for patients with severe to profound sensorineural hearing losses who receive little or no benefit from hearing aids. The implant basically takes over the function of the cochlear hair cells. The implant consists of external components (microphone, speech processor and transmitting coil) and internal components (receiver stimulator and electrode array). The implant is inserted via a trans mastoid facial recess approach to the round window and scala tympani.Objectives: to determine the effectiveness and safety of non fixation method in cochlear implantation.Methods: a prospective study carried out from September 2009 to September 2012 in Gazi Hariri Hospital. Eighty patients with congenital severe –profound sensorineural hearing loss prepared for cochlear implantation involved in the study and divided into 2 groups. Group A includes 40 patients in whom the internal device was fixed to the skull by nylon suture materials through small burr holes on both sides of the well. Group B includes 40 patients in whom the internal device placed in a tight sub pericranial pocket without nylon fixation to the skull. All patients followed postoperatively for 6 months observing wound healing and local complications (hematoma, infection, wound dehiscence, device extrusion and migration).Results: mean age 4.2 years and male-female ratio was 1.3:1.Group A: 1 patient (2.5%) developed minor wound infection treated conservatively. Three patients (7.5%) developedsevere wound infection with wound breakdown and device extrusion despite the use of antibiotics and local rotational flaps, the device was explanted in those 3 patients. Two patients (5%) developed hematoma without history of trauma and treated conservatively. One patient (2.5%) had device migration without affection of its function.Group B: 2 patients developed minor wound infection treated conservatively. One patient (2.5%) had severe wound infection ends up with wound dehiscence and device extrusion despite the use of antibiotics and local rotational flaps. Explantation of the device was done for this patient. Hematoma occurred in one patient (2.5%) without history of trauma and treated conservatively. Another one patient (2.5%) developed device migration without impairment of its function.Conclusion: creation of sub pericranial pocket without internal device fixation by nylon materials is an effective and reliable method in cochlear implantation without compromising the patient safety or device performance.Key words: cochlear implantation, non- fixation, sub pericranial pocket